UMKM DI KOTA PADANG DIHEMPAS COVID-19: ANTARA DILEMA DAN HARAPAN - Donna Ikranova Febrina (Jurnal Public Administration, Business and Rural Development Planning, 2020)
Usaha Mikro, Kecil, dan Menengah (UMKM) Padang City until the end of 2019 has an important role, in recruiting workers, and deciding the unemployment rate. Entering the beginning of 2020, all predictions collapsed. The Covid -19 outbreak has destroyed the economic order and undermined self-reliance. This research is structured using analytical descriptive method - a method that serves to describe objects, through samples that have been collected. Since the end of 2019 it is known that 40 thousand UMKM have been developed by the Padang City Government. Since Covid-19, as many as 10,468 UMKM from 11 sub-districts and 104 urban villages in Padang City have experienced shocks and cannot move - especially from the food industry sector. To break the chain that destroys UMKM, the Government is trying to provide debt, through the Sharia Financing Savings and Loan Cooperative, collaborating with BUMN, and others